Viceroy's house [videorecording (DVD)] - Chadha, Gurinder; Bonneville, Hugh; Anderson, Gillian, 1968-; Dayal, Manish, 1983- (IFC Films, 2017)
The final Viceroy of India, Lord Mountbatten, is tasked with overseeing the transition of British India to independence, but meets with conflict as different sides clash in the face of monumental change.